2016
DOI: 10.1111/cen.13056
|View full text |Cite
|
Sign up to set email alerts
|

Elevated PTH with normal serum calcium level: a structured approach

Abstract: Normocalcaemic hyperparathyroidism is a common biochemical finding, usually identified during an assessment of bone or renal health. Hypercalcaemia must be considered by calculation of adjusted calcium, and a careful history taken to assess dietary calcium intake and for the possibility of a malabsorption syndrome. 25-hydroxyvitamin D (25OHD) should be measured and replaced if indicated. The management plan for the patient is influenced by the context in which calcium and PTH were measured. In this brief revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…However, point-of-care (POC) testing with blood gas analyzers used to obtain ionised calcium level is not widely available in an outpatient setting and its use is hindered by other barriers such as precision, standardisation, special sample management and high cost 22 25. In view of these constraints and in keeping with its use in multiple other studies,6 8 13 14 serum albumin-adjusted total calcium continues to be measured and reported in many UK centres 26. However, we would certainly recommend confirmation of normocalcaemia with ionised calcium estimation if the albumin-adjusted value remains close to the upper limit of reference range and in patients with low albumin.…”
Section: Clinical and Laboratory Evaluationmentioning
confidence: 85%
See 1 more Smart Citation
“…However, point-of-care (POC) testing with blood gas analyzers used to obtain ionised calcium level is not widely available in an outpatient setting and its use is hindered by other barriers such as precision, standardisation, special sample management and high cost 22 25. In view of these constraints and in keeping with its use in multiple other studies,6 8 13 14 serum albumin-adjusted total calcium continues to be measured and reported in many UK centres 26. However, we would certainly recommend confirmation of normocalcaemia with ionised calcium estimation if the albumin-adjusted value remains close to the upper limit of reference range and in patients with low albumin.…”
Section: Clinical and Laboratory Evaluationmentioning
confidence: 85%
“…This consists of annual monitoring of albumin-adjusted or ionised calcium, PTH, vitamin D and renal function 5 47. Reassessment of bone density and nephrolithiasis at 3–5 year intervals has been recommended,26 although it may be more practical to adopt an individualised approach guided by the baseline measurements and overall risk profile for progressive bone disease. A 3-yearly reassessment to examine the sequential change in the bone density would certainly be recommended for patients with osteopaenia (T score between −1.0 and −2.5), those with multiple risk factors for osteoporosis or those with a high FRAX score at baseline.…”
Section: Management Strategy and Follow-upmentioning
confidence: 99%
“…However, there is no guideline for determining whether a PTH level in the normal range is in fact appropriately suppressed relative to the serum calcium or is non-suppressed. Additionally, authors have described a variant form of hyperparathyroidism in which PTH levels are elevated but calcium levels are normal [2][3][4][5][6][7]. Many patients with PHPT may be asymptomatic or have non-specific symptoms, leading to diagnostic uncertainty when only PTH or calcium is elevated.…”
Section: Introductionmentioning
confidence: 99%